Legal Protection for Consumers Who Lose Assets on Crypto Exchange Platforms in Indonesia: A Case Study of Hacking and Rug Pull - Dominic Imanuel Vidianto; Aloysius Mardiana; Nurul Hikmah; Aliif Ahmad Akbar (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2025)
This study analyzes legal protection for consumers who experience asset loss on crypto exchange platforms in Indonesia, focusing on two main issues: hacking and rug pull practices. The study examines existing regulations, such as the Electronic Information and Transactions Law (ITE Law) and the Financial Services Authority Regulation (POJK), and reviews two specific cases: hacking of the Indodax platform and rug pull of the ASIX token. The research method used is normative juridical, with a statutory and conceptual approach. The results of the study show that although these regulations exist, the implementation of legal protection remains weak, particularly in terms of security system supervision and the accountability mechanisms of platform providers. Therefore, this study recommends strengthening cybersecurity standards and applying stricter accountability principles by crypto platform providers. There is also a need for synchronization between existing regulations and increased consumer digital literacy to minimize risks arising from illegal practices in this sector.